The Relationship Between Anxiety and Managing Interpersonal Difference: Implications for Couples Counselling - John Meteyard; Kirsty Andersen Sr.; Denis O'Hara (Psychotherapy and Counselling Journal of Australia)
This study investigated the relationship between the capacity to manage and tolerate difference in others and trait anxiety. Data was provided from a sample of 173 students from an Australian higher education institution who completed The Emotional Reactivity Subscale of the Differentiation of Self Inventory-Revised (DSI-R), The State Trait Anxiety Inventory – trait (STAI-T), and The Tolerating Interpersonal Differences Subscale of the Differentiation Factor Inventory – Revised (DFI-R). Results reveal that trait anxiety when measured by both the STAI-T and DSI-R Emotional Reactivity Subscale, is a significant inverse predictor of the capacity to tolerate interpersonal differences within close relationships. Implications of these findings for the practice of couples therapy, including the role of relationship counsellors in helping their clients learn to more effectively manage difficult emotions like anxiety more effectively, are explored.